2021
DOI: 10.3390/ijms221910488
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Analysis of the Development of the Plant-Parasitic Cyst Nematodes Heterodera schachtii and Heterodera trifolii by Capillary Electrophoresis Time-of-Flight Mass Spectrometry

Abstract: The cyst nematodes Heterodera schachtii and Heterodera trifolii, whose major hosts are sugar beet and clover, respectively, damage a broad range of plants, resulting in significant economic losses. Nematodes synthesize metabolites for organismal development and social communication. We performed metabolic profiling of H. schachtii and H. trifolii in the egg, juvenile 2 (J2), and female stages. In all, 392 peaks were analyzed by capillary electrophoresis time-of-flight mass spectrometry, which revealed a lot of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Six supplements, including l -asparagine, l -hydroxyproline, para -aminobenzoic acid ( p ABA), vitamin B12, glutathione, and casein hydrolysate, were absent from AB169 (Additional file 9 : Table S3). Previous studies have shown that l -hydroxyproline and glutathione are associated with nematode growth and reproduction, mobility, and neurotransmission [ 45 ]. As a component essential for the synthesis of folate, p ABA is required for the development of parasites, such as Brugia malayi larvae and malaria [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Six supplements, including l -asparagine, l -hydroxyproline, para -aminobenzoic acid ( p ABA), vitamin B12, glutathione, and casein hydrolysate, were absent from AB169 (Additional file 9 : Table S3). Previous studies have shown that l -hydroxyproline and glutathione are associated with nematode growth and reproduction, mobility, and neurotransmission [ 45 ]. As a component essential for the synthesis of folate, p ABA is required for the development of parasites, such as Brugia malayi larvae and malaria [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that MS detection is usually crucial in metabolite analysis as many metabolites are not detectable optically without prior derivatization. Several CE-TOF methods have been successfully developed for various applications such as studying the metabolic profiling of cyst nematodes, investigating the metabolomic characteristics of macrophages infected with Leishmania amazonensis , exploring novel putative biomarkers of longevity in Caenorhabditis elegans, and examining skeletal muscle metabolites in lipoprotein lipase transgenic rabbits . Recent studies have also contributed to elucidating the metabolic pathways in human bodies associated with specific food intake and their connections to particular health conditions. , …”
Section: Applicationsmentioning
confidence: 99%